2016
DOI: 10.1093/jxb/erw289
|View full text |Cite
|
Sign up to set email alerts
|

Allantoin, a stress-related purine metabolite, can activate jasmonate signaling in a MYC2-regulated and abscisic acid-dependent manner

Abstract: Allantoin is a metabolic intermediate of purine catabolism that often accumulates in stressed plants. Recently, we used Arabidopsis knockout mutants (aln) of ALLANTOINASE to show that this purine metabolite activates abscisic acid (ABA) production, thereby stimulating stress-related gene expression and enhancing seedling tolerance to abiotic stress. A detailed re-examination of the microarray data of an aln mutant (aln-1) confirmed the increased expression of ABA-related genes and also revealed altered express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Despite the presence of polysaccharides distinct from those in terrestrial plants, SPE extraction from red seaweeds and subsequent MS analysis (Mikami et al, 2016) was similar in efficiency to those reported for terrestrial plants (wheat, Iehisa et al 2013Iehisa et al , 2014rice, Tsukahara et al 2015;barley, Rikiishi et al 2015 andHisano et al 2016; Arabidopsis, Lu et al 2015 andTakagi et al 2016). In the course of that work (Mikami et al, 2016), phytohormones were extracted from both lyophilized and fresh seaweed thalli after freezing in liquid nitrogen, which made the fresh samples easier to grind.…”
Section: Optimization Of Extraction Methodssupporting
confidence: 69%
“…Despite the presence of polysaccharides distinct from those in terrestrial plants, SPE extraction from red seaweeds and subsequent MS analysis (Mikami et al, 2016) was similar in efficiency to those reported for terrestrial plants (wheat, Iehisa et al 2013Iehisa et al , 2014rice, Tsukahara et al 2015;barley, Rikiishi et al 2015 andHisano et al 2016; Arabidopsis, Lu et al 2015 andTakagi et al 2016). In the course of that work (Mikami et al, 2016), phytohormones were extracted from both lyophilized and fresh seaweed thalli after freezing in liquid nitrogen, which made the fresh samples easier to grind.…”
Section: Optimization Of Extraction Methodssupporting
confidence: 69%
“…In particular, SWEET13, 332 which was strongly affected in our study, has been previously singled out as a target 333 for crop improvement in maize (Bezrutczyk et al, 2017). In explaining elevated cadmium and salt, through antioxidant mechanisms (Brychkova et al, 2008), and 345 jasmonic acid and ABA signalling (Takagi et al, 2016). Arabidopsis (Durand et al, 2017).…”
mentioning
confidence: 86%
“…3B), in agreement with the up-regulation of genes involved in ABA biosynthesis and response (Table II). It has been reported that MYC2 functions as a transcriptional activator of ABA signaling in Arabidopsis leaves under abiotic stress (Abe et al, 2003;Takagi et al, 2016). The crosstalk between ABA and JA has been shown to be regulated by MYC2 (Kazan and Manners, 2013).…”
Section: Increase Of Cks May Promote Shoot Growth In Am-and P I -Treamentioning
confidence: 99%